The hydrothermal process of aeolian sand and its thermal effect on permafrost in Qinghai-Tibetan Plateau considering rainfall and evaporation under climate warming - Lan, Tianli; Ma, Qinguo; Xia, Huxi; Luo, Xiaoxiao (Frontiers in Environmental Science, 2022)
As the heat exchange interface between atmosphere and permafrost, land cover regulates the influence of climate warming on permafrost. With the development of desertification on the Qinghai-Tibetan Plateau (QTP), aeolian sand has emerged as a significant environmental variable influencing the hydrothermal process of permafrost. To reveal the hydro-thermal process in aeolian sand and the thermal effect of sand layer on permafrost in the QTP, a coupled hydro-thermo-vapor model considering rainfall and evaporation was established, and the long-term hydrothermal variation of stratum covered by aeolian sand were analyzed. The results show that: (1) Aeolian sand layer is conducive to alleviating permafrost degradation. The alleviation effect is related to the sand layer thickness. (2) Water redistribution in sand layer and water accumulation in stratum are connected to sand layer thickness. Water accumulation in the thin sand layer is slight. However, acting as a permeability diode, the thick sand layer makes water accumulated in sand layer considerable and water storage in stratum increase. (3) As sand layer thickens, the equivalent heat conductivity (ETC) increases. The ETC of thin sand layer is higher in warm season than in cold season, while the ETC of thick sand layer is lower in warm season than in cold season. (4) In thin sand layer, heat convection and heat conduction are relatively small in the early stage, and heat conduction is the primary mode in the long term. In thick sand layer, heat transfer is dominated by heat convection and heat conduction in the early stage, but it is primarily reliant on heat convection in the long term.